Research principles for developing country food value chains - Reardon, Thomas; Sutradhar, Rajib; Gómez, M. I.; Barrett, Christopher B.; Buck, L. E.; De Groote, Hugo; Ferris, S.; Gao, H. O.; McCullough, E.; Miller, D. D.; Outhred, H.; Pell, A. N.; et al. (American Association for the Advancement of Science, 2011)
From farm to table, multidisciplinary research is needed to improve the economic benefit of food production in the developing world.